1977
DOI: 10.2118/5853-pa
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Steamflood Pilot in the Thick Monarch Sand of the Midway-Sunset Field

Abstract: This paper describes the design and development of a steamflood pilot consisting of six inverted five-spot patterns in Section 26C of the Midway-Sunsetfield. Steam injection will be in the 330-ft Monarch sand. A steamflood simulation study indicated a potential of 60- to 70-percent oil recovery and defined the relative importance of various steamflood parameters. Introduction The reservoir characteristics and production history of Section 26C of Midway-Sunset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…2, tar from the Street Ranch and Saner Ranch pilots is considerably more viscous than the tar from the Athabasca deposit and the heavy oil from the Midway Sunset d~posit. 5,6 Although the high initial viscosity of the south Texas tar presented a major obstacle for conventional production, we found that the viscosity of the tar could be decreased to acceptable levels at steamflood temperatures. Fig.…”
Section: San Miguel Tar Sand Depositmentioning
confidence: 81%
“…2, tar from the Street Ranch and Saner Ranch pilots is considerably more viscous than the tar from the Athabasca deposit and the heavy oil from the Midway Sunset d~posit. 5,6 Although the high initial viscosity of the south Texas tar presented a major obstacle for conventional production, we found that the viscosity of the tar could be decreased to acceptable levels at steamflood temperatures. Fig.…”
Section: San Miguel Tar Sand Depositmentioning
confidence: 81%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Table 1 is a summary of data for 14 projects that reported adequate information to perform a good history match. Table 2 and Fig.…”
Section: Comparison Of Model With Field Resultsmentioning
confidence: 99%
“…These 8 points are (1,1,1), (1,1,3), (1,3,1), (1,3,3), (3,1,1), (3,1,3) (3,3,1) and (3,3,3). Calculate the average of the 8 comer points and compare the average with y(2,2,2).…”
Section: Response Surface Methodologymentioning
confidence: 99%